2022
DOI: 10.1126/scirobotics.abi6745
|View full text |Cite
|
Sign up to set email alerts
|

Haptic perception using optoelectronic robotic flesh for embodied artificially intelligent agents

Abstract: Flesh encodes a variety of haptic information including deformation, temperature, vibration, and damage stimuli using a multisensory array of mechanoreceptors distributed on the surface of the human body. Currently, soft sensors are capable of detecting some haptic stimuli, but whole-body multimodal perception at scales similar to a human adult (surface area ~17,000 square centimeters) is still a challenge in artificially intelligent agents due to the lack of encoding. This encoding is needed to reduce the wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…In addition to solving classification problems, SVM holds the ability to estimate a continuous‐valued multivariate function, [ 92 ] which enables it to deal with regression tasks, including vibration sensing, [ 93 ] and force estimation. [ 20 ] Barreiros et al [ 20 ] reported a soft, optical, robotic flesh that was able to encode haptic stimuli and recognize contact force, position and gesture. SVM was used to regress the force, as well as classify touch location and gesture.…”
Section: Machine Learning For Analog Signalsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to solving classification problems, SVM holds the ability to estimate a continuous‐valued multivariate function, [ 92 ] which enables it to deal with regression tasks, including vibration sensing, [ 93 ] and force estimation. [ 20 ] Barreiros et al [ 20 ] reported a soft, optical, robotic flesh that was able to encode haptic stimuli and recognize contact force, position and gesture. SVM was used to regress the force, as well as classify touch location and gesture.…”
Section: Machine Learning For Analog Signalsmentioning
confidence: 99%
“…Reproduced with permission. [ 20 ] Copyright 2022, AAAS. c) KNN‐based foam posture recognition for detecting bend and twists and predicting angle.…”
Section: Machine Learning For Analog Signalsmentioning
confidence: 99%
See 3 more Smart Citations